Evolution of Uniportal Robotic‐Assisted Thoracic Surgery: A Retrospective Study on the Original and Modified Techniques for Lung Anatomic Resections - Ching Yang Wu; Ming Ju Hsieh; Yu Fu Wu; Diego Gonzalez‐Rivas; Chun Ting Kuo; Ching Feng Wu (Thoracic Cancer)
ABSTRACT Background Uniportal robotic‐assisted thoracic surgery (uRATS) has emerged as an innovative minimally invasive approach for lung anatomic resections. This study evaluates the safety, feasibility, and outcomes of uRATS, comparing the original technique with a modified approach utilizing a novel trocar configuration to minimize incision size. Methods A retrospective analysis was conducted on 40 patients who underwent uRATS for lung cancer between August 2023 and August 2024 at a tertiary medical center. The first 20 cases employed a 4 cm incision with three 8 mm trocars, while the subsequent 20 cases utilized a modified technique incorporating two flared trocars and a central 8 mm trocar, reducing the incision to 3.5 cm. Perioperative outcomes, postoperative pain, and complications were analyzed. Results The mean docking, console, and operative times showed no significant differences between the original and modified techniques. The mean postoperative pain scores and analgesic requirements were comparable. No conversions to multiport RATS, VATS, or open surgery were required. The most common complication was mild subcutaneous emphysema (5%). Learning curve analysis indicated that approximately 20 cases were needed to achieve technical proficiency. Conclusion uRATS is a safe and feasible approach for lung anatomic resections. The modified technique with flared trocars enables a smaller incision without compromising outcomes. Further studies are warranted to assess long‐term oncologic efficacy and cost‐effectiveness.